Letter from Charles T. Manatt - Charles T. Manatt:::::: (1971)
In this April 23, 1971 letter, Chairman Charles T. Manatt issues the official call to the California Democratic Party Reform Convention to be held May 15, 1971, in San Jose, focused exclusively on organizational reform. He explains that the convention follows more than two years of reform efforts, including recommendations from the California Commission on Democratic Party Reform, some already enacted and others referred to regional meetings for further input. Delegates are invited to participate in shaping a broader, more responsive, and united Democratic Party.